Trajectories of construction and training of a natural sciences teacher - Pereira, Gerlany de Fátima dos Santos (Seven Editora, 2024)
It is a text built under the aegis of the autobiographical perspective, with formative memorial clippings of a Professor of Natural Sciences, whose trajectory was crossed by the passion for Sciences, since her childhood. Throughout the construct, we narrate facts that rescue these memories and show how the Teacher in question was built and formed into a Teacher of Natural Sciences, who works at the higher level. DOI:https://doi.org/10.56238/sevened2024.010-071